(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
Centred on the case of a woman who felt ’surprisingly intense grief’ at the death of a tree in her garden, this article explores how our relationship with the other-than-human world around us can reveal experiential meaning and enable liberation. The discussion navigates between modern poetry, medieval Buddhism and Frankl’s logotherapy.